Kidney bioengineering by using decellularized kidney scaffold and renal progenitor cells. (February 2022) - Hsu, Chih-Yang; Chi, Pei-Ling; Chen, Hsin-Yu; Ou, Shih-Hsiang; Chou, Kang-Ju; Fang, Hua-Chang; Chen, Chien-Liang; Huang, Chien-Wei; Ho, Tzung-Yo; Lee, Po-Tsang
Highlights: Rat kidneys were decellularized by the perfusion of detergent. Acellular scaffolds preserved vascular, ureteric, cortical, and medullary architectures. The functional organ was regenerated by seeding progenitor and differentiated cells. The bioengineered kidney produced urine and reabsorbed albumin, glucose, and calcium. Abstract: Patients with end-stage renal disease often need dialysis to maintain their lives because of donor organ shortage. The creation of a transplantable graft to permanently replace kidney function would overcome the organ shortage problem and the morbidity associated with immunosuppression. In the present study, we decellularized rat kidneys by the perfusion of detergent, yielding acellular scaffolds with the vascular, uretic, as well as cortical and medullary architecture. To regenerate the functional organ, we seeded tubular epithelial cells and mouse kidney progenitor cells from the ureter together with endothelial cells and mouse kidney progenitor cells from the renal artery. The renal constructs from seeded cells were cultured in a whole-organ bioreactor. After 3 months of organ culture, the seeded cells formed renal tubules, grew in the glomeruli, and some mouse kidney progenitor cells were also scattered in the interstitium. We tested the function of the bioengineered kidney with standardized perfusate in vitro . The bioengineered kidney not only produced urine but also reabsorbed albumin, glucose, and calcium. We conclude that seeded cell-based bioengineering of kidneys with physiological secreting and reabsorbing properties is possible and holds therapeutic promise.